Development of Islamic Religious Education Curriculum to Prepare Religious Attitudes, Moderate, Inclusive, and Cultured Attitudes - RF, Firyal Yasmin; Nursobah, Asep (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
The purpose of the research in this article is to find out the basis for Minister of Religion Decree Number 183, namely preparing a Moderate, Inclusive, and Cultured attitude. The transition from time to time in the field of Islamic education has experienced many differences in understanding, especially in Indonesia which has a variety of recognized religions. Therefore, to face the dynamics that are constantly changing, unique innovations are needed, rooted in deep foundations, so that what is pursued can achieve its targets precisely. A foundation as a basis for curriculum development is very necessary. KMA Number 183 of 2019 has a new direction from the previous KMA, which was based on a moderate attitude. Researchers studied with a descriptive qualitative approach using content analysis techniques. This article aims to understand the philosophical basis of KMA 183 of 2019. Thus, the results of our study found that to obtain an attitude of mutual respect between understandings, as well as culture, namely by producing a generation that thinks rationally, creatively, and innovatively so that it can inherit cultural diversity and maintain it. to face the 21st Century.Tujuan penelitian pada artikel ini untuk mengetahui landasan pada Keputusan Menteri Agama Nomor 183 yaitu mempersiapkan sikap Moderat, Inklusif, dan Berbudaya. Perpindahan masa ke masa dalam bidang pendidikan Islam mengalami banyak perbedaan pemaham terutama di Indonesia memiliki ragam agama yang diakui. Oleh karena itu, untuk menghadapi dinamika yang tak henti-hentinya berubah, dibutuhkan inovasi-inovasi yang unik, berakar pada landasan yang mendalam, agar apa yang dikejar dapat mencapai sasarannya dengan tepat. Landasan sebagai dasar dalam pengembangan kurikulum sangat diperlukan. Pada KMA Nomor 183 tahun 2019 memiliki arah yang baru dari KMA sebelumnya, yang berlandaskan pada sikap moderat. Peneliti mengkaji dengan pendekatan kualitatif deskriptif menggunakan Teknik content analisis. Artikel ini bertujuan untuk memahami landasan filosofis pada KMA 183 tahun 2019. Dengan demikian hasil kajian kami lakukan ditemukan, untuk mendapatkan sikap saling menghargai antar paham, juga berbudaya yaitu dengan mencetak generasi yang berpikir rasional, kreatif, dan inovatif sehingga dapat mewariskan keragaman budaya serta menjaganya demi menghadapi Abad 21.